If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 432 = 7X Reorder the terms: 432 + X = 7X Solving 432 + X = 7X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-7X' to each side of the equation. 432 + X + -7X = 7X + -7X Combine like terms: X + -7X = -6X 432 + -6X = 7X + -7X Combine like terms: 7X + -7X = 0 432 + -6X = 0 Add '-432' to each side of the equation. 432 + -432 + -6X = 0 + -432 Combine like terms: 432 + -432 = 0 0 + -6X = 0 + -432 -6X = 0 + -432 Combine like terms: 0 + -432 = -432 -6X = -432 Divide each side by '-6'. X = 72 Simplifying X = 72
| 79-x=14+2x | | (x-4)(-2x+5)=0 | | 5(t-3)+5t=5(2t+4)-12 | | -3x+7=3x-11 | | in(6x)=3 | | (2x+4)+x=26 | | 4m-16=-9+3m | | 4m-10=-13+5m | | 30-x=12.5+4x | | 81b^4=18 | | 6(3+4x)-4=110 | | lx+ny+d=0 | | x-7.3=-3.4 | | 7x+6=5x-4 | | 20+55= | | 4mx-4y+6=0 | | Y=10+4x+x^2 | | 15x=2x+91 | | -2+y+3=5y+13 | | 4-7=y-4 | | 3(-4b)+6b=-12 | | 7x-5-6x=4 | | 2(X-1)+3=5 | | 13-16=4y+9-3y | | (8x^2+5x-1)-(8x^2+9)=30 | | 9(y-4)+3(y+3)=57 | | 5x^2+12x=2 | | -12=8-4y | | -5-5x+2=-10x+3-5x | | 6x=26.4 | | x^2=59.3 | | 11=-z+7 |